An exploration of sustainable innovation investment in emerging markets: An archival study - SeTin, SeTin; Martusa, Riki; Meythi, Meythi (International Journal of Management and Sustainability, 2024)
This study aims to examine the relationship between asymmetric cost behavior and innovation of listed firms in emerging markets, i.e., listed firms in the Indonesian capital market. The Sustainable Development Goals (SDGs) topic has become a hot issue worldwide. Innovation, as a part of SDGs, is a prerequisite to reducing the carbon emissions in a country, including the listed firms on the Indonesian capital market. This study employs quantitative method. To investigate Indonesian-listed firms investment in innovation, we use innovation scores from Thomson Reuters to investigate the investment in innovation by the Indonesian-listed firms. This study utilizes multiple regression tests to examine the empirical model. Our study uses an asymmetric cost behavior model to examine the investment from the firms. We apply data panel to examine the model, i.e., the listed firms of Indonesian capital market during 2010-2019. The result is that innovation influences asymmetric cost behavior. This study also performs a robustness check regarding the empirical model. The result shows that the model is robust. We contribute to the literature on sustainability accounting and the literature on the capital markets. The implication of this study is to give investors information related to the development of sustainability in developing markets. The developing market is a promising investment for investors worldwide. This study also gives feedback to regulators related to the development of innovation in developing markets, particularly Indonesian capital market.